PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS ATAS MEREK KOPI TORAJA DAN KOPI GAYO YANG DIDAFTARKAN OLEH NEGARA LAIN - Hamidi, Ayu Kumala Sari; Faniyah, Iyah (Universitas Ekasakti, 2019)
The existence of IPR, especially Geographical Indications and Brands, is the basis of policy making in the world of Trade. Indonesia is a country that is rich in potential Geographical Indication products and then Law No. 20 of 2016 concerning Geographical Indications and brands for National Regulations and in TRIPS as International Arrangements. but there are still violations of cases regarding Geographical Indications and Trademarks and occur in Toraja coffee and Gayo coffee. The formulation of the problem in this research is how is the trademark legal law for Geographical Indications in the case of Toraja coffee and Gayo coffee registered by other countries? How is the legal settlement of the Violation of Brand Geographical Indications carried out by other Countries against Toraja coffee and Gayo coffee?The specification of this study is Descriptive Analysis. The approach is a normative juridical approach using secondary data obtained through library studies. The data is then analyzed qualitatively and presented in a qualitative descriptive form. Based on the results of research and analysis, answers can be obtained: 1) Legal protection against Toraja coffee and Gayo coffee registered by other countries, namely by registering the trademark to the Director General of Intellectual Property Rights and after obtaining a Geographical Indication certificate from the Director General of Intellectual Property Rights, the geographical indication of a product's brand it gets strong protection. 2) Legal settlement of brand violations and geographical indications of the brand of Toraja coffee and Gayo coffee are litigation methods carried out through the Commercial Court institution, for Toraja Coffee to be carried out at the Ujung Pandang Commercial Court and Gayo Coffee at the Medan Commercial Court.